Hematopoietic cell transplantation in inborn errors of immunity - Part II: others - Fernandes, Juliana Folloni; Muratori, Rafaella; Loth, Gisele; Vieira, Ana Karine; Klinger, Paulo; Franco, Simone; Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Inborn errors of immunity (IEI) are a large, heterogeneous group of disorders resulting from deficiencies in immune system development and/or function, leading to increased susceptibility to infections, autoimmunity, autoinflammation, lymphoproliferation, and malignancy. Some diseases are classical hematopoietic cell transplantation (HCT) indications, such as Wiskott-Aldrich Syndrome, but more than 150 different IEI have been transplanted. Each disease and patient should be addressed individually as the clinical manifestations are variable, as well as the pre- and post-transplant care. This consensus strongly recommends that these patients are referred to experienced centers performing HCT for IEI.